Fabrication of highly dispersed Pd nanoparticles supported on reduced graphene oxide for solid phase catalytic hydrogenation of 1, 4-bis(phenylethynyl) benzene. (18th March 2020) - Zhu, Wanqiu; Guo, Yakun; Ma, Bangjun; Yang, Xiaojiao; Li, Yingjun; Li, Peilong; Zhou, Yuanlin; Shuai, Maobing
Abstract: In this work, nanopalladium catalysts supported on the surface of reduced graphene oxide ( r GO/Pd) with different palladium loadings have been prepared by one-step reduction in aqueous phase. They were mixed with 1, 4-bis(phenylethynyl)benzene (DEB) to form r GO/Pd-DEB composites according to a mass ratio of 1:3. It was shown that nanopalladium particles with particle size of about 2–6 nm were disperse uniformly on the surface of r GO when the Pd loadings were in the range of 3.97–10.60 wt%. The maximum hydrogen uptake capacity of r GO/Pd-DEB composites at 25 °C determined according to PCT method was about 182.5 ml/g after reacted with hydrogen for about 20 h, which was some lower than that of the common Pd/C-DEB pallet getter (216 ml/g) but significantly higher than alkynyl modified polyvinyl alcohol supported palladium hydrogen absorbing materials (0.32 ml/g), indicating that r GO/Pd could be used in solid phase catalytic hydrogenation due to the high dispersion of palladium nanoparticles and the physical proximity of r GO/Pd catalyst with DEB organic molecules. This provides a good potential technical way for perparing the moldable carbon aerogel hydrogen absorption materials. Graphical abstract: Image 1 Highlights: The r GO/Pd is efficient for solid catalytic hydrogenation of DEB. The r GO/Pd-DEB have a good hydrogen uptake capacity at room temperature. r GO and hydrogenated DEB layer have some hindering effect for hydrogen uptake rate.